Long -term antibacterial properties of fluoride-releasing orthodontic bonding adhesives - Ebubekir Toy; Erdem Hatunoglu; Fırat Ozturk; Sertac Aksakalli; Ugur Arslan (Cumhuriyet University, 2012)
Objectives: The aim of this study was to compare antibacterial properties of 3 different fluoride-releasing orthodontic adhesives during three months by using the direct contact test (DCT). Materials and Methods: The materials tested in the present study were Transbond Plus (3M Unitek, Monrovia, USA), Light Bond (Reliance Ortho Prod. Inc. Itasca, IL, USA), and Kurasper F (Kuraray Medical Inc., Okayama, Japan). Eight specimens of each material type were prepared for estimation. For the DCT, wells of 96-microtitre plates were coated with each of three bonding adhesives. Eight uncoated wells, using identical inocula size, served as a positive control (bacteria with medium). A Streptococcus mutans suspension was placed on the surface of each specimen that was held for 1 hour at 37°C. Bacterial growth was monitored for 16 hours with a temperature-controlled microplate spectrophotometer. The kinetics of the growth in each well was recorded continuously at 650 nm in every 30 minutes. Three additional measurements were performed on these tested materials after aging for 1 week, 1 month and 3 months. One-way ANOVA and Tamhane's T2 multiple comparison tests were applied to the data. The level of significance was set as p<0.05. Results: The DCT showed that there were significant differences found in freshly mixed samples between four groups (p<0.001, F=20.901). Freshly mixed samples of Transbond Plus showed antibacterial activity (p<0.001). Kurasper F and Light Bond did not differ from positive control. In the measurements of aged specimens, all materials showed an increase in the logarithmic growth rate of Streptococcus mutans. Conclusion: Only Transbond Plus showed antibacterial properties in freshly mixed specimens. However, none of the tested orthodontics composites showed antibacterial properties after aging.